2006
DOI: 10.1148/radiol.2382041930
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain: Prediction of Short-term Outcome of Facet Joint Injection with Bone Scintigraphy

Abstract: Bone scintigraphy with SPECT can help identify patients with low back pain who would benefit from facet joint injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 13 publications
2
129
0
3
Order By: Relevance
“…3 While most literature indicates that chronic morphologic changes of facet joints are not predictive of facet joint pain, 4 there is evidence that facet joint inflammation manifest as bone scan activity, facet joint hyperintensity on fat-suppressed T2-weighted MR imaging, or facet joint enhancement on gadolinium-enhanced MR imaging is predictive. 5,6 MR imaging evidence of facet joint signal change, defined as T2 hyperintensity or enhancement on fat-suppressed images, adjacent to compression fractures has not been characterized to date, to our knowledge. We hypothesized that evidence of facet joint signal change on MR imaging is more common in facet joints associated with an acute/subacute lumbar compression fracture than in facet joints adjacent to vertebral bodies that are either normal or have a chronic compression fracture.…”
mentioning
confidence: 94%
“…3 While most literature indicates that chronic morphologic changes of facet joints are not predictive of facet joint pain, 4 there is evidence that facet joint inflammation manifest as bone scan activity, facet joint hyperintensity on fat-suppressed T2-weighted MR imaging, or facet joint enhancement on gadolinium-enhanced MR imaging is predictive. 5,6 MR imaging evidence of facet joint signal change, defined as T2 hyperintensity or enhancement on fat-suppressed images, adjacent to compression fractures has not been characterized to date, to our knowledge. We hypothesized that evidence of facet joint signal change on MR imaging is more common in facet joints associated with an acute/subacute lumbar compression fracture than in facet joints adjacent to vertebral bodies that are either normal or have a chronic compression fracture.…”
mentioning
confidence: 94%
“…Overall, facet joint signal change on fat-suppressed MRI did not always correlate with increased studies purport that bone scan activity on 99m Tc-MDP single photon emission tomography/computed tomography ( 99m Tc-MDP SPECT) can predict both painful facet joints and positive response to percutaneous treatment (5,6). However, this assertion is unproved; these studies used intra-articular injections, which have a high placebo rate, rather than comparative medial branch blocks, the standard diagnostic method for facet joint pain accepted by pain medicine physicians (7).…”
Section: Resultsmentioning
confidence: 92%
“…This approach was used because it reflects actual clinical practice in which facet joint evaluation is a subjective comparison of target activity to background activity within areas of normal bone. The dichotomous approach was used to facilitate comparison with MRI and because a dichotomous approach has been used in prior studies of facet joint bone activity for guidance of percutaneous treatment (5,6).…”
Section: Image Analysismentioning
confidence: 99%
“…Studies of older adults [24] [25] demonstrated that the presence of degenerative facet pathology in older adults is ubiquitous, but higher radiographic severity scores were associated with the presence of low back pain. Pneumaticos et al [26] reported that patients with a SPECT prior to therapeutic infiltration of the zygapophysial joints had better pain scores one month after injection. Furthermore, the number of joints treated with injection decreased by up to two-thirds compared with the suggestions of the referring physician.…”
Section: Discussionmentioning
confidence: 99%